The Effect of Marketing Mix On “KPR Xtra Bebas” Decision Making in Bank X Regional I - Arthur, Kevin Michael; Asmara, Alla; Simanjuntak, Megawati (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The rapid growth of mortgages affected Bank X to launch product innovation